Penggunaan Kartu Kata Digital Untuk Meningkatkan Kemampuan Membaca Permulaan Pada Anak Tunarungu Kelas V di SLB Paulus Tomohon - Sidik, Talha Y.; Siwi, Femmy D.; Undap, Tiersa R.; Kiriweno, Henny B. A. (Jurnal Ilmiah Wahana Pendidikan, 2026)
The purpose of this study is to find out whether the word digtal card can improve the ability to read beginning in deaf children in grade V at SLB Paulus Tomohon. Through the use of digital word card media, the background of this research is the low initial reading ability of deaf students who still have difficulty recognizing letters, syllables, and simple words. The learning media used so far is still conventional so that it does not attract the attention of students. Therefore, interactive and visual media innovations are needed to facilitate the learning needs of deaf children. This study uses the Single Subject Research (SSR) Method with an A-B-A design, namely Baseline 1 (A1), Intervention (B), and Baseline 2 (A2). The subject of the study was one deaf student in class V at SLB Paulus Tomohon. The research instrument consisted of an initial reading ability test, observation sheets, and field notes. Data was collected through direct observation during the implementation of learning using digital word card media, then analyzed by calculating the average score, percentage increase, and level change between conditions. The results of the study show that the use of digital word cards can improve the initial reading ability of deaf students. It is shown that the overlap data in the analysis between conditions A1/B and B/A2 is 0%, which means that the smaller the percentage of overlap shows the greater the influence on the target behavior. This is also supported by an increase in the initial reading ability score obtained by children during the baseline 1, intervention, and baseline 2 phases. In the intervention-1 phase, children get a frequency score of 48, in the intervention phase, children get scores of 60, 72.5, 75, 75.90, 90, and in the baseline-2 phase, children get a score of 91.25, 91.25, 91.25, 91.25, 91.25, 91.25, 91.25. Thus, it can be concluded that digital word card media is effectively used to improve early reading skills in deaf children, because it is able to attract attention, motivate learning, and provide a visual and interactive learning experience according to the characteristics of deaf students